Foliar uptake, accumulation, and distribution of cadmium in rice (Oryza sativa L.) at different stages in wet deposition conditions. (1st August 2022) - Xu, Zhangqian; Zhu, Zhen; Zhao, Yuhua; Huang, Zhi; Fei, Jiangchi; Han, Yongliang; Wang, Maodi; Yu, Pengyue; Peng, Jianwei; Huang, Ying; Fahmy, Ahmed E.
Abstract: Atmospheric deposition of cadmium (Cd) in rice ( Oryza sativa L.) has become a major global concern. Foliar uptake allows vegetables to accumulate heavy metals from the atmosphere, but this has rarely been studied in rice. Therefore, this study investigated the Cd accumulation in rice growing at different exposure periods (the tillering, booting, heading, and maturity stages) under a wet deposition of CdCl2 ·2.5H2 O solution through pot experiments. The Cd concentrations in leaves, roots, husk, brown rice, and leaf structures were analyzed to explore foliar uptake, accumulation, and distribution of Cd in rice tissues at different growth stages. The results showed that wet deposited Cd can be absorbed on the rice leaf surface and remains on the leaves for a long time. The sequence of Cd accumulation in rice tissues was: leaves > brown rice > husk > roots, with leaves accounting for greater than 71.78% of the total accumulation. The accumulation of wet deposited Cd in leaves, husk, and brown rice had large temporal variations between the four typical stages. There was no significant variations in Cd content in roots between different growth stages. Correspondingly, the foliar uptake of Cd was rarely transported from the leaves via the phloem to roots. Conversely, the foliar uptake of Cd was transported upwards to grains. The accumulation of Cd fluctuated with each growth stage, initially increasing and then decreasing at the heading stage and finally reaching a peak at the maturity stage. The highest total accumulation of Cd in both the high and low wet deposition conditions occurred at maturity, resulting in 15.53 and 11.23 μg plant −1, respectively. These results provide theoretical support for further research into identifying efficient foliar control measures to reduce Cd accumulation and maintain food safety. Graphical abstract: Image 1 Highlights: Investigating the foliar uptake and accumulation of Cd in rice in wet deposition. Cd was absorbed on the surface of leaves and remained for a long time. Cd significantly accumulated in leaves, husks, and grains, but not in roots. Highest total Cd accumulation under wet deposition occurred at the maturity stage. For food safety, more research into Cd contamination via foliar uptake is vital.